Innovation Model for Implementation of Public Tourism Policy in Pamekasan Regency Case Study of Talang Siring Beach - Cahyono, Jordan Putra; Wijanarko, Andri; Idialis, Alifah Rokhmah (EDUTOURISM Journal Of Tourism Research, 2024)
This study aims to determine the implementation of tourism development policies and the role of public policies in tourism development in Pamekasan, especially Talang Siring Beach. This research is reviewed through four aspects of public policy implementation developed by Edwards, namely communication, resources, disposition and bureaucracy. A type of qualitative research with an analytical descriptive approach to identify some fundamental things regarding tourism policy in Pamekasan. Based on research, the implementation of tourism development policies in Pamekasan has gone very well although it still leaves a number of problems. Meanwhile, the role of public policy plays a very important role even though there is still something to be addressed. This research also concluded that the ideal tourism policy model to implement is community-based tourism. Some of the obstacles that can be identified are lack of synergy (communication) between stakeholders, lack of competence of policy implementers, and lack of community participation. Meanwhile, on the other hand, high commitment from local political leaders and the support of good resource facilities are factors supporting the policy.